1998
DOI: 10.1007/s004390050847
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphic 43Thr bcl-2 protein confers relative resistance to autoimmunity: an analytical evaluation

Abstract: We have found a novel polymorphic (Ala43Thr; ACC-->GCC) bcl-2 allele in a Japanese population. An in vitro expression study with a mouse IL-7-dependent pre-B cell line has revealed that inhibition of the programmed cell death function of 43Thr bcl-2 protein is suppressed compared with that of normal 43Ala bcl-2 protein. Since bcl-2 expression in B-lymphoid cells elicits autoimmune disease in mice, we have investigated the possibility of whether a bcl-2 polymorphism has a different susceptibility to autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…Also, the anti-apoptotic molecule, bcl-2, maps to the IDDM6 region. One Japanese study 137 has reported an association of T1D with an Ala43Thr polymorphism of BCL2; however, this association has not been confirmed in a recent study of different Caucasoid populations. 138 Several loci on chromosome 2q have been linked to T1D.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 85%
“…Also, the anti-apoptotic molecule, bcl-2, maps to the IDDM6 region. One Japanese study 137 has reported an association of T1D with an Ala43Thr polymorphism of BCL2; however, this association has not been confirmed in a recent study of different Caucasoid populations. 138 Several loci on chromosome 2q have been linked to T1D.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 85%
“…Although 28/51 unique non-synonymous mutations were marked 'benign' by PolyPhen, this does not preclude a functional role. For example, non-synonymous mutations at residue A43 were scored as 'benign' by PolyPhen; but previous work 47 has shown that changes at this position provide resistance to autoimmunity via reduction of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since synergistic effects of Bcl-2 genotypes and cytokine abnormalities have been reported to predispose to disease expression, 41,42 further dissection of the mechanisms and regulation of propriocidal and cytokine-induced cell death may lead to a better understanding of the pathogenesis of SLE. …”
Section: Discussionmentioning
confidence: 99%